Chiari Malformation Type 1 and Syringomyelia in a Patient With Prior Surgically-Treated Sagittal Synostosis Effectively Treated With Posterior Cranial Vault Distraction Osteogenesis. Issue 6 (September 2021) - Feller, Christina N.; Jensen, John N.; Lew, Sean M.
Abstract : Abstract: The presenting report describes the use of a posterior cranial vault distraction procedure in resolving a Chiari malformation with associated syringomyelia following a surgically-treated nonsyndromic craniosynostosis. Chiari malformations are typically treated with posterior fossa decompression with or without expansion duraplasty. The objective of this report is to describe the effectiveness in resolving both Chiari malformation and secondary syringomyelia with posterior cranial vault distraction osteogenesis. A 5-year-old male, with a history of surgery for sagittal synostosis during infancy, presented with daily severe headaches and dysesthesias in the hands and feet. Imaging demonstrated a copper-beaten calvarium and a Chiari 1 malformation with a 7 mm diameter C4-T1 syrinx. He underwent posterior cranial vault distraction osteogenesis over 3 months to increase his intracranial volume. The patients' headaches improved significantly, and his dysesthesias resolved postoperatively. A magnetic resonance imaging performed 7 months after completion of distraction demonstrated resolution of the Chiari malformation and decompression of his syrinx. A computed tomography scan at 9 months postdistraction showed resolution of the copper-beaten calvarium. Patients with a history of craniosynostosis can develop inadequate cranial volume over time due to abnormal skull growth, leading to secondary Chiari malformation with or without syringomyelia. Posterior vault distraction is an effective strategy to address these conditions and can be employed later in childhood to treat the underlying pathology. The mechanism potentially expands both calvarium and dura, which in turn addresses both the Chiari malformation and secondary syringomyelia.